2008
DOI: 10.1111/j.1742-7843.2007.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Metyrapone and Mifepristone Reverse Recognition Memory Loss Induced by Spontaneous Morphine Withdrawal in Mice

Abstract: Morphine withdrawal leads to an increase in corticosterone concentration in plasma, and cognitive deficits are found after withdrawal. Evidence indicates that glucocorticoid hormones affect memory. The aim of the current study was to evaluate the effects of metyrapone and mifepristone on memory deficit following spontaneous morphine withdrawal. Memory was tested by using the object recognition task. The novel object recognition task was carried out in a square wooden open-field apparatus using objects. The tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Corticosterone, carbenoxolone, and mifepristone were obtained from Sigma-Aldrich (St. Louis, MO, USA). Doses of carbenoxolone and mifepristone were chosen based on previous research describing their ability to antagonize HSD2 (Heine & Rowitch, 2009) and the GC receptor (Mesripour et al, 2008) respectively. Corticosterone and mifepristone were dissolved in a sesame oil vehicle prior to injection whereas all other drugs were dissolved in sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…Corticosterone, carbenoxolone, and mifepristone were obtained from Sigma-Aldrich (St. Louis, MO, USA). Doses of carbenoxolone and mifepristone were chosen based on previous research describing their ability to antagonize HSD2 (Heine & Rowitch, 2009) and the GC receptor (Mesripour et al, 2008) respectively. Corticosterone and mifepristone were dissolved in a sesame oil vehicle prior to injection whereas all other drugs were dissolved in sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…Mifepristone has been shown to reduce reinstatement of ethanol-seeking and escalated drinking in two different animal models (66, 166). Furthermore, mifepristone has been shown to be effective at reducing the self-administration of amphetamine (167), cocaine (168, 169), morphine (170), and ethanol (57, 66, 162, 166, 171175). A recent study also demonstrates the effectiveness of mifepristone in reducing withdrawal symptoms of alcohol (176).…”
Section: Pharmacotherapeutic Strategiesmentioning
confidence: 99%
“…The anti-GC activity of mifepristone has made it a potential treatment for Cushing's syndrome (Johanssen and Allolio, 2007) and neurological and psychological disorders (DeBattista and Belanoff, 2006;Gallagher and Young, 2006;Gallagher et al, 2005Gallagher et al, , 2008Wulsin et al, 2010;Young, 2006). The drug has also been examined in the self-administration of amphetamine (De Vries et al, 1996), cocaine (Deroche-Gamonet et al, 2003;Fiancette et al, 2010), morphine (Mesripour et al, 2008), and ethanol, where it has been shown to have either no effect or decrease baseline ethanol consumption (Fahlke et al, 1995;Jacquot et al, 2008;Koenig and Olive, 2004;Lowery et al, 2010;O'Callaghan et al, 2005;Roberts et al, 1995;Yang et al, 2008). However, the role of mifepristone in stress-induced reinstatement of ethanol-seeking is not known.…”
Section: Introductionmentioning
confidence: 99%